The Influence of Financial Literacy on Students’ Personal Financial Management in the Digital Era - Dini Pratiwi; Vemi Fytaloka (Universitas Muhammadiyah Palu, 2025)
This study examines the influence of financial literacy on students’ personal financial management in the digital era, with evidence from universities in South Sumatra. Financial literacy is increasingly important as students are exposed to diverse financial products and digital platforms such as e-wallets, QR-based payments, and online credit services. A quantitative research design was employed, with data collected from 385 students across public and private universities in South Sumatra using purposive sampling. The research instrument measured students’ financial literacy in budgeting, saving, credit management, and digital financial tools, as well as their financial management practices in planning, saving, and controlling expenses. Data were analyzed using multiple linear regression. The findings indicate that financial literacy has a positive and significant effect on students’ personal financial management. The regression model explains 34.4% of the variance in financial management behavior, suggesting that while financial literacy is essential, other factors such as self-control, lifestyle, and income also play a role. The study contributes to the literature by integrating digital financial literacy into the analysis of personal financial management and provides practical implications for universities and policymakers to strengthen financial education. These findings emphasize the urgent need for financial literacy programs tailored to the digital financial ecosystem to ensure sustainable financial behavior among Generation Z students.